Flexible Honeycombed Nanoporous/Glassy Hybrid for Efficient Electrocatalytic Hydrogen Generation. Issue 49 (17th October 2019) - Li, Rui; Liu, Xiongjun; Wu, Ruoyu; Wang, Jing; Li, Zhibin; Chan, K. C.; Wang, Hui; Wu, Yuan; Lu, Zhaoping
Abstract: Hydrogen evolution reaction (HER) in alkaline media urgently requires electrocatalysts concurrently possessing excellent activity, flexible free‐standing capability, and low cost. A honeycombed nanoporous/glassy sandwich structure fabricated through dealloying metallic glass (MG) is reported. This free‐standing hybrid shows outstanding HER performance with a very small overpotential of 37 mV at 10 mA cm −2 and a low Tafel slope of 30 mV dec −1 in alkaline media, outperforming commercial Pt/C. By alloying 3 at% Pt into the MG precursor, a honeycombed Pt75 Ni25 solid solution nanoporous structure, with fertile active sites and large contact areas for efficient HER, is created on the dealloyed MG surface. Meanwhile, the surface compressive lattice‐strain effect is also introduced by substituting the Pt lattice sites with the smaller Ni atoms, which can effectively reduce the hydrogen adsorption energy and thus improve the hydrogen evolution. Moreover, the outstanding stability and flexibility stemming from the ductile MG matrix also make the hybrid suitable for practical electrode application. This work not only offers a reliable strategy to develop cost‐effective and flexible multicomponent catalysts with low Pt usage for efficient HER, but also sheds light on understanding the alloying effects of the catalytic process. Abstract : A free‐standing honeycombed nanoporous/glassy sandwich hybrid is developed through dealloying metallic glass (MG) precursor. The honeycombed Pt‐rich nanoporous structure providing fertile active sites and large contact areas combined with the introduced compressive lattice‐strain on the surface gives rise to better hydrogen evolution activity. Furthermore, the ductility of the intermediate MG matrix contributes to the excellent flexibility of the hybrid.